Postbiotic Modulation of Retinoic Acid Imprinted Mucosal-like Dendritic Cells by Probiotic Lactobacillus reuteri 17938 In Vitro - Haileselassie, Yeneneh; Navis, Marit; Vu, Nam; Qazi, Khaleda Rahman; Rethi, Bence; Sverremark-Ekström, Eva (Frontiers in Immunology, 2016)
Lactobacilli are widely used as probiotics with beneficial effects on infection-associated diarrhea, but also used in clinical trials of e.g., necrotizing enterocolitis and inflammatory bowel diseases. The possibility of using probiotic metabolic products, so-called postbiotics, is desirable as it could prevent possible side effects of live bacteria in individuals with a disturbed gut epithelial barrier. Here, we studied how Lactobacillus reuteri DSM 17938 cell-free supernatant (L. reuteri-CFS) influenced retinoic acid (RA)-driven mucosal-like dendritic cells (DC) and their subsequent effect on T regulatory cells (Treg) in vitro. RA clearly imprinted a mucosal-like DC phenotype with higher IL10 production, increased CD103 and CD1d expression, and a downregulated mRNA expression of several inflammatory-associated genes (NFκB1, RELB, and TNF). Treatment with L. reuteri-CFS further influenced the tolerogenic phenotype of RA-DC by downregulating most genes involved in antigen uptake, antigen presentation, and signal transduction as well as several chemokine receptors, while upregulating IL10 production. L. reuteri-CFS also augmented CCR7 expression on RA-DC. In cocultures, RA-DC increased IL10 and FOXP3 expression in Treg, but pre-treatment with L. reuteri-CFS did not further influence the Treg phenotype. In conclusion, L. reuteri-CFS modulates the phenotype and function of mucosal-like DC, implicating its potential application as postbiotic.